NORMATIVE ANALYSIS OF SUPERVISORY REGULATIONS IN VILLAGE HEAD ELECTIONS: ENSURING LEGAL CERTAINTY IN SUMEDANG REGENCY - Ryan Syaifurrakhman; Sarip Sarip; Elya Kusuma Dewi (CV. Barokah Publsiher, 2026)
Indonesia’s constitutional system guarantees the implementation of local democracy through the mechanism of Village Head Elections. Within the framework of Indonesia as a state governed by the rule of law, all aspects of Village Head Elections should ideally be conducted based on the principle of legal certainty, including the aspect of supervision. However, there are normative deficiencies in the regulatory framework governing supervision in Village Head Elections, as reflected in various legal instruments, including laws, Minister of Home Affairs regulations, as well as regional and regent regulations as their implementing provisions. This study aims to analyze the regulatory framework governing the implementation of Village Head Elections in Sumedang Regency, particularly from the perspective of supervisory practices, and to examine it within the framework of constitutional law. The research employs a normative legal method with statutory and conceptual approaches. The legal materials used consist of statutory regulations containing norms related to the implementation of Village Head Elections, as well as relevant constitutional law doctrines. The findings indicate that, with regard to the supervisory aspect, the regulatory framework governing Village Head Elections in Sumedang Regency does not yet provide clear, systematic, and comprehensive norms concerning supervisory institutions, the scope of supervisory authority, or mechanisms for handling violations. This condition creates the potential for legal uncertainty, undermines the principles of local democracy, and contradicts the fundamental tenets of the rule of law. Therefore, strengthening the regulatory framework on supervision in the implementation of Village Head Elections is necessary to ensure legal certainty and to enhance the quality of democratic governance at the village level.